Characterization of the wake of a submarine propeller via Large-Eddy simulation. (30th April 2019) - Posa, Antonio; Broglia, Riccardo; Felli, Mario; Falchi, Massimo; Balaras, Elias
Highlights: The wake of a submarine propeller was studied via Large-Eddy Simulation Detailed comparisons with experiments showing good agreement Wake populated by vortices shed from the suction side of the propeller blades Stronger coherence of the structures shed from the inner radii of the blades Streamwise evolution of turbulence at outer radii featuring local maxima Abstract: Results of large-eddy simulations of a submarine propeller in open-water (isolated) configuration are presented for three load conditions. An immersed boundary approach is adopted to handle the rotating geometry of the propeller within a stationary cylindrical grid composed of about 840 million nodes. Direct comparisons with Particle Image Velocimetry experiments conducted in parallel demonstrate that the simulations reproduce the wake very accurately. In particular the wake dynamics are mainly dominated by tip and hub vortices. Strong structures are also shed in the near wake from the suction side of the propeller blades, correlating with local maxima of turbulent kinetic energy. However, they are not a long standing feature of the propeller wake. In contrast, helical structures originating form the root of the propeller blades are more persistent and their footprint is still visible few propeller diameters downstream. We verified that load conditions affect substantially both hub vortex and tip vortices. In a similar way, for increasing loads turbulent kinetic energy experiences a faster growth at the wake axis, populated by the hub vortex, compared to the outer radii, dominated by the tip vortices. Also, the evolution of turbulent kinetic energy at the outer edge of the wake is not monotonic, in contrast with that in the wake core, due to mutual interaction and associated shear between tip vortices and the wake of the following blades.